Ideal Teacher: A Framework of Teachers’ Competencies - jufriadi, jufriadi; Lestari, Alia; Firman, Firman (Graduate School of Universitas Negeri Malang, 2023)
Abstract: This study aims to (1) describe the characteristics of an ideal teacher based on the results of a literature review, and (2) create a competency map and indicators for an ideal teacher. Data of this study were obtained from various primary sources including literature reviews, documents and results of interviews with 10 experienced teachers. The data were analyzed qualitatively by using thematic analysis. This study shows that there are at least seven main competencies that should be possessed by a teacher which include (1) Intellectual competence (2) Pedagogical competence (3) Professional Competence (4) Intrapersonnel competence. (5) Interpersonal Competence (6) Leadership Competence and (7) Spritual Competence. This study also proposed 66 (sixty six) indicators as the characteristics of the seven competencies of ideal teacher.Abstrak: Penelitian ini bertujuan untuk (1) mendeskripsikan karakteristik guru ideal berdasarkan hasil kajian pustaka, dan (2) membuat peta kompetensi dan indikator guru ideal. Data dari penelitian ini diperoleh dari berbagai sumber primer antara lain kajian pustaka, dokumen dan hasil wawancara dengan 10 orang guru berpengalaman. Data dianalisis secara kualitatif dengan menggunakan analisis tematik. Kajian ini menunjukkan bahwa setidaknya ada tujuh kompetensi utama yang harus dimiliki oleh seorang guru yang meliputi (1) Kompetensi Intelektual (2) Kompetensi Pedagogik (3) Kompetensi Profesional (4) Kompetensi Intrapersonal. (5) Kompetensi Interpersonal (6) Kompetensi Kepemimpinan dan (7) Kompetensi Spiritual. Penelitian ini juga mengusulkan 66 (enam puluh enam) indikator sebagai ciri dari tujuh kompetensi guru ideal.